Persistent efficacy of 3.5% doramectin compared to 3.15% ivermectin against gastrointestinal nematodes in experimentally-infected cattle in Brazil - Lopes, Welber Daniel Zanetti [UNESP]; dos Santos, Thaís Rabelo [UNESP]; Sakamoto, Claudio A.M. [UNESP]; de Lima, Roberto Cesar Araújo [UNESP]; Valarelli, Rodrigo Lechugo; Paiva, Pablo; da Costa, Alvimar José [UNESP] (Elsevier, 2013)
The present study aimed to evaluate the persistent efficacy of a 3.5% doramectin* (700μg/kg) formulation compared to 3.15% ivermectin** (630μg/kg) treatment, administered subcutaneously at a dose of 1mL/50kg body weight in cattle experimentally infected with gastrointestinal nematodes. Seventy-two male crossbred Holstein cattle that were negative for helminth infection were divided into nine groups. Treatments of 3.5% doramectin (Groups 2, 4, 6 and 8) and 3.15% ivermectin (Groups 3, 5, 7 and 9) were administered on days 49, 42, 35 and 28 prior to challenge with infectious nematode larvae (L3). Animals in the control group (Group 1) received saline solution on day 49 before challenge. Beginning on day zero, each animal received 50mL orally of a mixed culture containing approximately 3,000 third stage larvae (L3) of Haemonchus (60%), Oesophagostomum (20%), Cooperia (15%) and Trichostrongylus (5%) for seven consecutive days, resulting in a total challenge of 21,000 larvae/animal. Due to the large number of cattle, autopsies were performed between days 28 and 35 after the last day of inoculation. The formulation containing doramectin (700 mcg/kg) achieved persistent efficacy against H. placei and C. punctata for 49 and 35days, respectively. The persistent efficacy of ivermectin (630 mcg/kg) against H. placei lasted for 49days, but this treatment was ineffective against C. punctata. Both formulations demonstrated persistent efficacy against T. axei for 49days. The persistent efficacy of doramectin (700 mcg/kg) and ivermectin (630 mcg/kg) lasted for 49 and 42days against O. radiatum, respectively. © 2012 Elsevier Ltd.
Keywords: Cattle nematodes; Doramectin; Endectocide; Ivermectin; Persistent efficacy; doramectin; ivermectin; ivomec gold; sodium chloride; treo ace; unclassified drug; animal experiment; animal tissue; autopsy; Brazil; cattle; controlled study; Cooperia; cross breeding; drug efficacy; gastrointestinal infection; haemonchosis; Haemonchus; inoculation; larva; male; nematodiasis; nonhuman; oesophagostomiasis; Oesophagostomum; treatment outcome; trichostrongyloidiasis; trichostrongylosis; Trichostrongylus; Animals; Anthelmintics; Cattle; Cattle Diseases; Gastrointestinal Diseases; Male; Nematoda; Nematode Infections; Animalia; Bos; Cooperia punctata; Haemonchus placei; Oesophagostomum radiatum; Trichostrongylus axei; Vermes